Factores sociodemograficos y su relación con actividad sexual en el programa de adultos mayores del centro de salud José Quiñones de Chiclayo - Rodriguez Zuñiga, Karina Elizabeth (2017)
This research aims to determine the relationship between socio-demographic factors: age, sex, marital status, pathology, and sexual activity in the program for seniors in the health center of Chiclayo Jose Quinones , December-January 2016, is a research observational , analytical descriptive, cross-sectional, the sample universe consists of 37 older adults who met the criteria for inclusion and exclusion, to collect information on a sheet of collection of demographic data was used and the Survey of sexual activity in the elderly it was built by Muñoz et al. (2002 ), validated in the Department of Public Health of the Catholic University of Santiago, Chile. As a result he found : The sexual activity of adults is necessarily linked to coital activity in 73.3 % of those who consider 36.7 % said good quality of sexual intercourse , and 73.7 % as good frequency of sex , whose relations they are spontaneous in 86.7 % single stimulation in addition to 62.5 % which can be reflected in their self- perceived quality of life considering the sexuality of the elderly in a comprehensive and holistic manner, including both physical and emotional factors due to certain modifications of the sexual pattern.